Comprehensive Review of 3D Concrete Printing by Using Ground Granulated Blast-Furnace Slag - Jamalulail, Nur Syahera; Salleh, Norhafizah (Recent Trends in Civil Engineering and Built Environment, 2021)
3D building printing is a technology for producing 3D models of an object to build of any shape or size in layers by using computer software. The development of 3D printing was going to be more famous and commercial in the future in order to reduce the construction cost and labor demands, sustainability, and to the greenest way. Concrete is the mixture that consist the ingredients of water, binder (cement) and aggregates (rock, sand, gravel). The productions of Portland cement in construction leads to the emissions of carbon dioxide (CO2) gas into the air. Waste material has been used as cement replacement in this research study in order to reduce the carbon dioxide (CO2) gas emissions. This research study was going to evaluate the viability of concrete for 3D printing and printing emphasizing the impact on potential opportunities of this innovative industry. The behaviour of 3D concrete printing and potential of modified mortar in 3D concrete mix design by using Ground Granulated Blast-Firnace Slag (GGBS) is used in order to evaluates the potential uses of GGBS in concrete mixture for 3D building printing. This research study involved the review of concrete compressive strength and workability of 3D concrete printing with the control aspect during process manufacturing. The result show that the mix design of 3D concrete printing with 30% and 40% produced concrete strength of 47.33MPa and 47.67MPa respectively. Furthermore, control aspect requirements of concrete for 3D printing were discussed in the field extrudability, flowability, buildability, strength between layers, aggregates, and water-cement ratio. Throughout of this study, the manufactures of 3D building printing materials using environmentally friendly elements can contribute effectively create a sustainable environment automatically.